Implementación de un banco de pruebas para la determinación de la rigidez dieléctrica del aceite del transformador. - Salazar Loor, Robinson Vladimir (2023)
Carrying out the dielectric strength test of insulating oil and other materials used in electrical equipment is essential to ensure its quality, offering the necessary safety and reliability to this equipment, which includes transformers, circuit breakers, and reactors, for example. In the present project, information regarding the standards used to determine how the dielectric strength of the oil that serves as an insulating material and as a coolant is analyzed, dissipating the heat generated by the coils and the core of an electrical transformer to the outside. The ASTM 877D standard was used to carry out different tests to measure the dielectric breakdown of the oil with a Huazheng HZJQ-1B machine, where two types of oil samples were analyzed by means of the controlled increase of voltage values until it reaches its threshold value. Of rupture. A new oil and an already used one were used in a transformer's insulating and cooling system. A user guide for handling the Huazheng HZJQ-1B machine was also made, because it is a new device and it lacked information about how to use it and what are the steps to carry out the tests in the measurement of the oil's dielectric strength.